E-COMMERCE PERLENGKAPAN BELADIRI MAESTRO SEMARANG BERBASIS WEB (Information Technology and Telematics, 2016)
Abstract- Maestro Semarang sales process is still using the conventional system that customers who want to buy and seek out new products from Maestro Maestro Semarang came directly to Semarang to find and select items to be purchased. In addition to these factors, expand the sales area by opening stores in other areas also need a substantial amount of funds because of the cost of rental stores, labor costs, the cost of ancillary equipment and other costs compared to alternative web-based sales or e-commerce. Objectives to be achieved is to make e-commerce that can help facilitate the sales process and transact remotely on Maestro Semarang. Method of system development using the waterfall with the early stages of the system, system analysis, system design using UML and implementation of systems using PHP and MySQL. The results of this research are e-commerce in Semarang Maestro can help the sales process, the promotion process and make it easier to transact remotely on Maestro Semarang Keywords – E-Commerce,Maestro Semarang, PHP, MySQL